99.6k views
3 votes
PLEASE HELP IM SUPER BEHIND GEOMETRY 25 PTS

PLEASE HELP IM SUPER BEHIND GEOMETRY 25 PTS-example-1
PLEASE HELP IM SUPER BEHIND GEOMETRY 25 PTS-example-1
PLEASE HELP IM SUPER BEHIND GEOMETRY 25 PTS-example-2
PLEASE HELP IM SUPER BEHIND GEOMETRY 25 PTS-example-3
User Mrege
by
6.1k points

1 Answer

1 vote

Answer:

1)
\therefore f^(-1)(x)=(1)/(2)x^2-3,\:x\ge0.

2)
f^(-1)(x)=\sqrt[4]{x-16},\:x\ge16

3)
f^(-1)(x)=(8)/(3)x-(8)/(3)

Explanation:

1) The given function is
f(x)=√(2x=6),\:\:x\ge-3.

Let
y=√(2x-6).

Interchange x and y to get:


x=√(2y+6).

Square both sides;


x^2=2y+6.

Solve for y.


x^2-6=2y.


(1)/(2)x^2-3=y.


\therefore f^(-1)(x)=(1)/(2)x^2-3,\:\:x\ge0.

2) The given function is
f(x)=x^4+16,\:\:x\ge0

Let
y=x^4+16

Interchange x and y;


x=y^4+16

Solve for y


x-16=y^4


\sqrt[4]{x-16}=y,

Therefore the inverse is


f^(-1)(x)=\sqrt[4]{x-16},\:x\ge16

3) The given function is
f(x)=(3x)/(8)+1

Let
y=(3x)/(8)+1

Interchange x and y


x=(3y)/(8)+1

Solve for y:


x-1=(3y)/(8)


8x-8=3y


(8)/(3)x-(8)/(3)=y

Therefore the inverse is


f^(-1)(x)=(8)/(3)x-(8)/(3)

User Jessica D
by
7.2k points